(3GdeNJGQ ef cJGH Gdefi hGdShd aj TQM CSeGA GdMSfi heOM TeGFd GdQShds - (3CHh HcQ Hf CHj Ydj Hf SGde GdJfhNj GdMdHjs
(3ChdgG (B:s
(3GdMeO ddg Pi GdbhI GdJi dGJQGe hGdYRg GdJi dG JVGe hHYO aEf cfJ aief dgL HPcQ CSeGA Gddg JYGdi GdMSfi s
(3BNQgG (B:s
(3hJhai Udi Gddg Ydjg hSde hgh GHf KdGK hSJjf SfI cGedI s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjOGfjI ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(130) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs